2008
DOI: 10.1021/jf0724926
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Barley Malt Protein Modification on Beer Foam Stability and Their Relationship to the Barley Dimeric α-Amylase Inhibitor-I (BDAI-I) as a Possible Foam-Promoting Protein

Abstract: The foam stability of beer is one of the important key factors in evaluating the quality of beer. The purpose of this study was to investigate the relationship between the level of malt modification (degradation of protein, starch, and so on) and the beer foam stability. This was achieved by examining foam-promoting proteins using two-dimensional gel electrophoresis (2DE). We found that the foam stability of beer samples brewed from the barley malts of cultivars B and C decreased as the level of malt modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 42 publications
(96 reference statements)
4
51
0
1
Order By: Relevance
“…In terms of protein Z, it seems that the Z4 component correlated with improved foam performance, whereas the reverse was observed for protein Z7 65 . It has been suggested that protein Z and an α-amylase inhibitor correlate positively with foam whereas yeast-derived thioredoxin was possibly foam negative 66,107 . The foam stability due to proteins reflects a balance between the respective levels of polypeptides derived from hordein and the albuminoid polypeptides Z and LTP1 17 .…”
Section: Foam Chemistrymentioning
confidence: 99%
“…In terms of protein Z, it seems that the Z4 component correlated with improved foam performance, whereas the reverse was observed for protein Z7 65 . It has been suggested that protein Z and an α-amylase inhibitor correlate positively with foam whereas yeast-derived thioredoxin was possibly foam negative 66,107 . The foam stability due to proteins reflects a balance between the respective levels of polypeptides derived from hordein and the albuminoid polypeptides Z and LTP1 17 .…”
Section: Foam Chemistrymentioning
confidence: 99%
“…BDAI-1, α-amylase/trypsin inhibitors CMb, probable trypsin-inhibitor CMe2.2, BMAI-1, α-amylase tetrameric inhibitor CMa and subtilisin-chymotrypsin inhibitor CI-1A have been identified in twice-foamed foam 67 . Among them, only BDAI-1 has been recognized as a foam-promoting protein 78,124 . The foam stability of different beer samples and comercial lager beers has been described by their levels of protein Z and BDAI-1 78 .…”
Section: Foam Formation and Stabilizationmentioning
confidence: 99%
“…The majority of the beer proteins have been identified as PRs 67,79,130 . Proteome maps have also been used in beer quality control to associate particular beer proteins and respective beer quality traits [77][78][79]124 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could affect beer foam quality and participate in haze formation. BDAI-1 is assumed to be a foam promoting protein 140,243 , while BTICMe influences beer haze stability [284][285][286] . A proteomics study by Iimure 139 suggests that BDAI-1, CMb and CMe are growth factors of colloidal haze.…”
Section: Chymotrypsin/subtilisin Inhibitors (Ci-1 and Ci-2)mentioning
confidence: 99%